2012
DOI: 10.1111/j.1600-6143.2011.03955.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Hyperacute Rejections in the Absence of Detectable Complement Activation in a Patient With Endothelial Cell Reactive Antibody

Abstract: This case involves a 54-year-old patient with polycystic kidney disease and a history of hyperacute allograft rejections. Two previous compatible live donor transplants functioned immediately but failed within the first 12 h due to antibody-injury. This patient was referred for a third transplant due to decreased vascular access and progressive hypotension from uremic autonomic dysfunction. He was broadly sensitized to HLA; however, a live donor was identified through kidney paired donation for whom he had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…We and others have reported hyperacute rejections in patients positive for AECAs with no detectable HLA-DSA. 13,20 Thus, there is growing evidence that antibody-induced endothelial cell activation, independent of complement, may be sufficient for immune cell recruitment and microvascular injury. Three of the AECA targets identified in this study (endoglin, EDIL3, and FLT3) have been implicated in endothelial activation and leukocyte extravasation, and these findings are consistent with our in vitro data showing that AECA stimulation of endothelial cells results in the upregulation of adhesion and HLA molecules and the production of inflammatory chemokines and cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have reported hyperacute rejections in patients positive for AECAs with no detectable HLA-DSA. 13,20 Thus, there is growing evidence that antibody-induced endothelial cell activation, independent of complement, may be sufficient for immune cell recruitment and microvascular injury. Three of the AECA targets identified in this study (endoglin, EDIL3, and FLT3) have been implicated in endothelial activation and leukocyte extravasation, and these findings are consistent with our in vitro data showing that AECA stimulation of endothelial cells results in the upregulation of adhesion and HLA molecules and the production of inflammatory chemokines and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we reported that these antiendothelial cell antibodies (AECAs) are enriched for IgG2 and IgG4, which are IgG subclasses that activate complement poorly or not at all. 12,13 In contrast, identification of AECAs in recipients with broad HLA sensitization or in those undergoing HLA-incompatible transplantation was associated with an increased incidence and severity of antibody-mediated rejection (AMR).…”
mentioning
confidence: 99%
“…However, a number of observations suggest that non-HLA reactive antibodies also contribute to pre-sensitization and may influence the overall graft outcome (79). Cases of early humoral rejection in the absence of detectable donor-specific antibodies (DSA) have also been reported (10, 11). In a landmark collaborative transplant study, Opelz and colleagues revealed the association between high panel reactive antibodies (PRA) before transplantation and late graft loss in recipients of kidney transplants from HLA identical siblings (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of observations suggest that non-HLA reactive antibodies also contribute to pre-sensitization and may influence the overall graft outcome (7)(8)(9). Cases of early humoral rejection in the absence of detectable donor-specific antibodies (DSA) have also been reported (10,11). In a landmark collaborative transplant study, Opelz and colleagues revealed the association between high panel reactive antibodies (PRA) before transplantation and late graft loss in recipients of kidney transplants from HLA identical siblings (12).…”
Section: Introductionmentioning
confidence: 99%